The Strategy process : concepts, contexts, and cases - Quinn, James Brian; Mintzberg, Henry ;James, Robert M. (New Jersey : Prentice-Hall, 1988)
Each CEO (Chief Executive Officer) shares with all other CEOs the challenge of guiding his organization through the unfolding future of the world about him. Success will depend on his ability to perceive and understand his world in all its subtlety, inconsistency, bureaucracy and political maneuver as well as its rationality, in other words, in all of its complexity.
Part 1. Strategy. The strategy concept -- The strategist -- Formulating strategy -- Strategy analysis -- Strategy formation -- Part 2. Organization. Dealing with structure and systems -- Dealing with power -- Dealing with culture -- Part 3. Context. Achieving configuration -- The entrepreneurial context -- The mature context -- The diversified context -- The innovation context -- The professional context -- Managing transition -- Thinking strategically.
Includes bibliographical references and index.
Keywords: COMPANIES -- MANAGEMENT -- STRATEGY -- ESSAYS